Miocene Range Growth Along the Altyn Tagh Fault: Insights From Apatite Fission Track and (U‐Th)/He Thermochronometry in the Western Danghenan Shan, China. Issue 8 (29th August 2019) - Yu, Jingxing; Zheng, Dewen; Pang, Jianzhang; Wang, Yizhou; Fox, Matthew; Vermeesch, Pieter; Li, Chaopeng; Xiao, Lin; Hao, Yuqi; Wang, Ying
Abstract: The left‐lateral strike‐slip Altyn Tagh fault that defines the northern margin of the Tibetan Plateau plays a crucial role in accommodating the Cenozoic deformation related to the growth of plateau. However, the slip history along the fault remains highly debated. Here we report new 14–16 Ma apatite fission track (AFT) and 9–11 Ma apatite (U‐Th)/He (AHe) data in the western Danghenan Shan, north Tibet. Age‐elevation relationships and AFT/AHe age differences suggest a period of rapid exhumation with an average rate of 0.1–0.3 km/Ma from 16 to 9 Ma for this area. Thermal history modeling indicates that this was preceded by accelerated exhumation between the late Oligocene and middle Miocene ( 15 Ma). A northward increase in AFT ages and asymmetric topography across the western Danghenan Shan indicate that the uplift and exhumation are mainly controlled by the thrust fault along the southern flank of the western Danghenan Shan. As the thrust fault is a branch of the Altyn Tagh fault, the rapid exhumation probably represents onset of the transition along the Altyn Tagh fault from left‐slip motion to crustal shortening in the Dangnenan Shan region. Our findings show that the middle Miocene deformation is not only recorded in the middle and northern Qilian Shan but also in the southwestern portion of the Qilian Shan, which favors a synchronous middle‐Miocene deformation model for the entire Qilian Shan. Key Points: New apatite fission track and (U‐Th)/He data reveal rapid exhumation in the western Danghenan Shan since 15 Ma Rapid movement along the Altyn Tagh fault began at least 15 Ma The north Tibet has experienced two‐stage deformation in the Cenozoic